2006
DOI: 10.1016/j.stam.2005.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts for hydrogen generation from water vapor

Abstract: Phosphate glasses dissociating hydrogen from water vapor were prepared and their performance was evaluated. Glasses with compositions of 30Na 2 O-10BaO-30P 2 O 5 -(30Kx)Nb 2 O 5 -xWO 3 (5!x!25) dissociated water vapor into hydrogen and oxygen around 500 8C. The best dissociation performance was observed on a specimen with the tungsten composition of xZ15. The result suggests that the coexistence of Nb 2 O 5 and WO 3 is important in obtaining a high performance of hydrogen dissociation. When Nb 2 O 5 was replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The splitting of water molecules can also be provided by heat obtained from a nuclear reactor or a concentrating solar system, such as a solar tower, solar trough, linear Fresnel system or dish system [ 1 ]. The direct decomposition of water driven by heat can be released using thermocatalytic processes [ 9 ]. The most promising and useful approach for large-scale hydrogen production is based on thermochemical cycles—redox, sulfur-iodine, copper-chlorine and others [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The splitting of water molecules can also be provided by heat obtained from a nuclear reactor or a concentrating solar system, such as a solar tower, solar trough, linear Fresnel system or dish system [ 1 ]. The direct decomposition of water driven by heat can be released using thermocatalytic processes [ 9 ]. The most promising and useful approach for large-scale hydrogen production is based on thermochemical cycles—redox, sulfur-iodine, copper-chlorine and others [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies [5,6] have reported that phosphate glasses that incorporate tungsten oxide have the ability to absorb hydrogen protons in their structure. This capability results from the trapping of an electron by the W 6+ ions which induces W 5+ states and promotes the dissociation of the hydrogen atom and the adsorption of its proton.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that some phosphate glasses containing tungsten oxide decompose water vapor and absorb hydrogen [2,3]. Spectrometric studies on these glasses showed that the glasses had absorption bands in the IR and visible (600-650 nm) regions, which were assigned to the vibration mode of O-H and the absorption by W 5+ ion, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these phosphate glasses are expected to be good proton conductors as well as catalysts for water vapor decomposition. Moreover, it has been suggested in the previous study that the addition of transition metal ions such as Nb is important for water vapor decomposition [3]. Therefore, to develop new functional glass catalysts and electrolytes it seems important to investigate the mechanisms of water vapor decomposition and proton conduction in the phosphate glasses with WO 3 and Nb 2 O 5 .…”
Section: Introductionmentioning
confidence: 99%